2015
DOI: 10.1167/iovs.14-16322
|View full text |Cite
|
Sign up to set email alerts
|

Tumor Regression After Brachytherapy for Choroidal Melanoma: Reduction of Thickness and Cross-Sectional Area by Shape and Regression Pattern

Abstract: Heterogeneity in RP, variation in shape, and tumor cross-sectional area as an alternative measure must be considered when tumor regression rate is used in outcome analysis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 50 publications
0
15
0
1
Order By: Relevance
“…The current study has no sufficient power for evaluating the type of regression pattern. 34,35 According to the radiation dose, the application of 106 Ru plaque brachytherapy is limited by a steep dose-gradient in tissue, with the upper limit of penetration judged to be approximately 5 mm. 14,36 That is to say, in 106 Ru plaques (as compared with 125 I or 103 Pd), the dose deposition of the plaque to the basal part of the tumor can be nine times more than that of the apex dose.…”
Section: Discussionmentioning
confidence: 99%
“…The current study has no sufficient power for evaluating the type of regression pattern. 34,35 According to the radiation dose, the application of 106 Ru plaque brachytherapy is limited by a steep dose-gradient in tissue, with the upper limit of penetration judged to be approximately 5 mm. 14,36 That is to say, in 106 Ru plaques (as compared with 125 I or 103 Pd), the dose deposition of the plaque to the basal part of the tumor can be nine times more than that of the apex dose.…”
Section: Discussionmentioning
confidence: 99%
“…Our research found that, for example, the reference instructions of Investigative Ophthalmology & Visual Science stipulate that a title of the book be written in the normal typeface (ARVO, 2015) while the title was actually written in italics in the published articles. Examples include references 46 and 47 in the introduction of the already-mentioned article on the regression of the tumour Melanoma (Rashid et al, 2015). Vaccine does not require in its citation instructions that the issue of the journal be given.…”
Section: Discussionmentioning
confidence: 99%
“…If the instructions did not contain a citation instruction or an example bibliographical reference for some type of resource, a citation of the given resource published in the relevant year of the particular journal was used. For example, reference 37 in the article "Tumor Regression After Brachytherapy for Choroidal Melanoma" served as an example of a bibliographical reference to a contribution to an edited book, because Investigative Ophthalmology & Visual Science does not provide any example in its citation instructions (ARVO, 2015;Rashid, Heikkonen, & Kivelä, 2015). In this way, 17 examples of bibliographical references were made for individual journals and the NLM citation style.…”
Section: Methodsmentioning
confidence: 99%
“…For extrafoveal, small-to medium-sized choroidal melanomas of the middle periphery, brachytherapy turned out to be successful, and its equality to enucleation in terms of patient survival was confirmed by the prospective Collaborative Ocular Melanoma Study (COMS) using iodine-125 [12]. Ruthenium-106 brachytherapy (RBT) for the treatment of uveal melanoma was introduced by Lommatzsch and Vollmar in 1966 and is now commonly applied [13][14][15][16][17][18][19]. Due to a steep, axial dose fall-off (10% isodose at 6.8 mm depth) damage to remote eye structures can be minimized [15].…”
Section: Introductionmentioning
confidence: 99%